Effect of co-encapsulation using white and red onion peel extract on the viability and stability of Lacticaseibacillus rhamnosus under stressful conditions - Afaf Ejaz; Yuosra Amer Ali; Muhammad Afzaal; Farhan Saeed; Aftab Ahmed; Sadaf Waliat; Muhammad Umar Farooq; Aasma Asghar; Faiyaz Ahmed; Mahbubur Rahman Khan (PLoS ONE, 2025)
The study aimed to probe the effect of white and red onion extract on the viability and stability of encapsulated probiotics under stressed conditions. Intentionally, white and red onion peel extract was obtained and used with wall materials to encapsulate the probiotic. Symbiotic microcapsules were characterized for their morphological, molecular, and in vitro attributes. Similarly, free and co-encapsulated probiotics cells were also subjected to a simulated gastrointestinal assay. The SEM images demonstrated the successful encapsulation of Lacticaseibacillus rhamnosus within sodium alginate, along with white and red onion extract. The FTIR spectra showed the intermolecular interaction between the components of microcapsules. The in vitro assay showed that co-encapsulated probiotics showed better survival compared to free cells. In a nutshell, the co-encapsulation with red and white onion extract is an effective approach to enhance the viability of probiotics under stressed conditions.